Urgensi Bimbingan Penyuluhan Islam (BPI) Dalam Membentuk Karakter Remaja di Lingkungan Tembelok Kelurahan Mandalika Kecamatan Sandubaya Kota Mataram - Ilhami, Ahmad Fahmi Wahyu; Fakhri, Moh. (Jurnal Ilmiah Global Education, 2024)
This research aims to determine the urgency of Islamic counseling guidance in shaping the character of teenagers and to find out the supporting and inhibiting factors for implementing the urgency of Islamic counseling guidance in shaping the character of teenagers in the Tembelok Neighborhood, Mandalika Village, Sandubaya District, Mataram City. This research uses a qualitative approach. This approach is used so that the author can gain a broad and in-depth understanding of the urgency of BPI in shaping the character of teenagers in the Tembelok Neighborhood, Mandalika Village, Sandubaya District, Mataram City. The research results show that Islamic Counseling Guidance (BPI) is very important. First, BPI helps direct teenagers to the path of goodness with strong supervision from parents and religious figures. Second, BPI instills religious values ​​from an early age to direct youth's piety and faith. Third, BPI helps develop an attitude of awareness in teenagers with love, patience and coaching. Meanwhile, supporting and inhibiting factors in shaping adolescent character include the existence of Islamic Counselors and the active role of religious and community leaders as supporting factors, while environmental complexity, difficulty in controlling adolescent self-control, character formation from an early age or during puberty, negative environmental impacts, and lack of affection. from parents as an inhibiting factor.